POLA PENGELOLAAN PROGRAM CSR UNTUK MENINGKATKAN DAYA SAING UMKM - Eviatiwi Kusumaningtyas Sugiyanto; Sri Yuni Widowati; Ratna Wijayanti (Jurnal Dinamika Sosial Budaya, 2017)
The purpose of this study is to provide insight into how the management pattern of CSR programs that can improve the competitiveness of SMEs. The method used is qualitative research with phenomenological approach. The informants were chosen based on purposive, consisting of the Social Fund Management Team of Central Java Bank, the recipients of the UMKM program, and the intellectuals who will be represented by the academics. The results showed that the pattern of CSR leads to the form of partnership with the concept of community development. The form of partnership requires the participation between donors and beneficiaries. While the program formed through CSR of human resources, production and technology and financial capabilities